Ontology-Based Support for Complex Events - Sasa, A.; Vasilecas, O. (Elektronika ir Elektrotechnika, 2011)
With increasing demands for agility and reactivity, scientific circles and leading ICT companies have recognized the need for EDA(event-driven architecture) and complex event processing in factory automation, signal processing, data acquisition, manufacturing, andother applications of industrial electronics. We propose an EDA framework for defining and processing complex events based onontologies. The main novelty of our approach is introduction of semantic aspects into EDA. Our framework enables highly expressivesemantic definitions of complex events and a higher level of semantic integration of real-time events with the domain and eventontologies. The main component of the framework is the complex event service that acts as an event sink for member events and as anevent source for inferred complex events. Our approach is complementary to existing approaches and can enhance their support forcomplex events that require higher expressivity and semantic descriptions. Ill. 4, bibl. 22, tabl. 1 (in English; abstracts in English andLithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.618